Manusia, Kesejahteraan, dan Ekonomi Digital - Novia Utami; Yogie Pranowo (Sapientia Humana: Jurnal Sosial Humaniora, 2022)
Everyone wants to live a prosperous life. However, in the pursuit of well-being, wrong decisions are often made due to either psychological or rational reasons. Living in the digital era where everything is easier does not necessarily make this process error-free. The digital economy has been a vital part of the strategy to achieve well-being. Amidst the process, the digital economy finally found its place in the metaverse where people can interact with others in a virtual but seemingly real way. A bibliometric analysis was carried out in this literature review.  Results show that humans need to continuously improve themselves before they can finally implement all their financial plans and achieve well-being. At the same time, given how critical innovation is for success, humans need to keep innovating. One of the ways to innovate is to implement digitalization principles in every aspect of life. In addition, it is also important to focus and improve adoption of metaverse principles to direct human intentional behavior to well-being